"Emotions in Cultural Dynamics": What Non-Humans Can Teach Us about the Role of Emotions in Cultural Evolution. (April 2022) - Dezecache, Guillaume; Sievers, Christine; Gruber, Thibaud
The role emotions play in the dynamics of cultural phenomena has long been neglected. The collection of articles recently published in Emotion Review provides an important first step into this necessary endeavor. In this commentary, we discuss this contribution by emphasizing the role epistemological parsimony should play in the future of this research agenda. The cultural behavior and emotions of chimpanzees is taken as reference.